2002
DOI: 10.2494/photopolymer.15.265
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Orientation of Mesogenic Moieties in Photo-Cross-Linkable Copolymer Liquid Crystals by Irradiation with Polarized Light.

Abstract: Three kinds of methacrylate polymer liquid crystals (PLCs); a copolymer PLC (PLC) substituted with a photo-cross-Linkable 4-(4'-methoxycinnamoyl)oxybiphenyl (MCB) side group and a 4-methoxybiphenyl (4MB) side group (P1), a CPLC with a MCB side group and a 4-cyanobiphenyl (4CN) side group (P2) , and a PLC with a photocross-linkable 4-cinnamoyloxybiphenyl side group (P3), are synthesized . The thin films of these polymers are applied to a birefringent film by irradiation with linearly polarized ultraviolet (LPUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Flexible side chains attached to the conjugated backbone support facile deposition, improve flexibility, and increase the mobilities. Methoxy biphenyl (MeOBP) was selected as the mesogen for this study due to its thermotropic behavior with high thermal stability and lamellae forming behavior. In previous studies of homopolymers and copolymers of MeOBP, lamellar stacking has been observed in both crystalline and smectic phases. The ability of the biphenyl moiety to undergo π stacking in the crystalline and smectic phases enables the formation of well-defined microdomains .…”
Section: Introductionmentioning
confidence: 99%
“…Flexible side chains attached to the conjugated backbone support facile deposition, improve flexibility, and increase the mobilities. Methoxy biphenyl (MeOBP) was selected as the mesogen for this study due to its thermotropic behavior with high thermal stability and lamellae forming behavior. In previous studies of homopolymers and copolymers of MeOBP, lamellar stacking has been observed in both crystalline and smectic phases. The ability of the biphenyl moiety to undergo π stacking in the crystalline and smectic phases enables the formation of well-defined microdomains .…”
Section: Introductionmentioning
confidence: 99%